Indonesian EMI Teachers’ Challenges: Voices from Primary Education Teachers - Zanuba Jamilatul Ula Al Hikmah; Budi Setyono; Asih Santihastuti (Jurnal Manajemen Pendidikan dan Ilmu Sosial, 2026)
English Medium Instruction (EMI) is widely implemented in Indonesian primary schools, especially in international schools, to improve students' international competitiveness. But the rapid growth of EMI is not necessarily supported by teacher and school readiness, particularly at the primary level, where students are still mastering language skills. The study explores the issues teachers encounter in implementing EMI in Indonesian primary schools. This study used a qualitative narrative inquiry methodology, interviewing three teachers from an international primary school in Indonesia. A thematic analysis (Braun & Clarke, 2006) was used to analyse the data. Five key challenges were identified: language proficiency, professional development, classroom dynamics, institutional and cultural challenges, and affective challenges. These challenges are inter-related and impact the teaching and learning process. The study revealed that support is needed in terms of teacher training, school policy, and practices that are sensitive to the contextual factors. This research adds to the scant research on EMI in primary education in Indonesia and has implications for teacher preparation and school policies.